Relationship of vitamin D, fibrinogen and their ratio with acute coronary syndrome: A comparative analysis of unstable angina, NSTEMI, and STEMI - Himayat Ullah; Sarwat Huma; Muhammad Ashraf; Nafisa Tahir; Ghulam Yasin; Mohammed Yunus; Hossam Shabana; Mohamed Ahmed Muharram; Abdulrahman H. Shalaby; Ahmed Ali Hassan Ali; Mohamed Elwan Mohamed Mahmoud; Ahmed Mahrous Ahmed Ibrahim; et al. (PLoS ONE, 2025)
Background There is emerging evidence suggesting that vitamin D and fibrinogen play contrasting roles in ACS pathophysiology and their combined impact, expressed as the vitamin D/fibrinogen ratio, can be a potential biomarker for ACS severity. This study aimed to investigate the relationship between vitamin D, fibrinogen, and their ratio with ACS types, and assess their potential as risk stratification biomarkers. Methods This multicenter observational study was conducted in tertiary care hospitals in Afghanistan, Egypt, and Pakistan, including 300 ACS patients. Serum vitamin D and fibrinogen levels were measured using electrochemiluminescence immunoassay and the Clauss method, respectively. Statistical analyses included ANOVA, Kruskal-Wallis, post-hoc Games-Howell tests, Spearman’s correlation, Fisher’s Z-test, and multivariable logistic regression. Results Vitamin D levels were significantly lower (p < 0.001) and fibrinogen levels significantly higher (p < 0.001) in STEMI patients compared to NSTEMI and UA. The vitamin D/fibrinogen ratio showed a stronger correlation with ACS severity (Spearman’s rho = −0.45, p = 0.01) than vitamin D alone (−0.41, p = 0.01), but this difference was not statistically significant (Fisher Z = 0.34, p = 0.73). Logistic regression revealed that a 1 nmol/L increase in vitamin D reduced ACS severity by 7.1% (p = 0.043), while a unit increase in the vitamin D/fibrinogen ratio reduced severity by 6.2% (p = 0.048). Conclusion The contrasting effects of vitamin D and fibrinogen can prove useful biomarkers and modifiable risk factors for ACS. The superiority of the vitamin D/fibrinogen ratio over vitamin D only, however, needs further validation in larger studies.